Influence of the handball goal anti-tip system through the game actions observation method: 2019 Four Nations international handball junior tournament - Baena-González, R.; Lozano, D.; Gallardo, A. M.; Chavarria-Ortiz, C.; Garcia-Tascón, M. (International Journal of Performance Analysis in Sport, 2020)
The anti-tip system used in the goals for the practice of handball begins to be considered a relevant factor to avoid accidents, as factors such as misuse, lack of maintenance, etc., can cause accidents with serious and even fatal damage. Therefore, the aim of this study is to analyse the influence in the handball game of an innovative anti-tip system for the goals (ATS) called Tutigool. For the analysis of game actions the free software Lince has been used, which allows data analysis of the multidimensional observation proposal called the Game Action Observation System influenced by the anti-tip system of the goals (SOATS) composed of 11 criteria and 41 categories of all the influential variables in the offensive actions of the sport. Results show that goals were moved in 25.64% of the 117 body contacts, 93.3% of those 30 movements were caused by the goalkeeper, 66.7% of the displacements occurred after the player`s throw, which means 78 times and the goalkeeper`s body impulse on the goal was the main reason of moving with 36.8% meaning 43 times. This innovative system should be considered and included in the handball regulation to improve the safety and avoid accidents of the practitioners.